Nonlinear trajectory-tracking control of an autonomous underwater vehicle. (15th November 2017) - Karkoub, Mansour; Wu, Hsiu-Ming; Hwang, Chih-Lyang
Abstract: In this study, a hierarchical robust nonlinear (HRN) controller is designed for the trajectory-tracking of an autonomous underwater vehicle (AUV) subject to uncertainties (e.g., current disturbances, unmodeled dynamics and parameter variations). The proposed HRN controller respectively utilizes the back-stepping and sliding-mode control technique with hierarchical structure based on the kinematic and dynamic models of the system. Both trajectory-tracking and virtual velocity control of the AUV are achieved with guaranteed asymptotic stability. An initial study was performed based on a simplified 4 degree-of-freedom model for the AUV to evaluate the viability of the proposed approach. Simulations results showed excellent performance of the AUV closed-loop system. A 6 degree-of freedom model of the AUV system was later developed and an HRN controller was designed for trajectory tracking of the AUV. The robustness of the proposed HRN controller was verified through injection of random uncertainties into the system model. The closed-loop stability of the proposed individual subsystems is respectively guaranteed to have uniformly ultimately bounded (UUB) performance based on the Lyapunov stability criteria. Furthermore, computer simulations have shown that the overall closed-loop system with an HRN controller achieves good asymptotic tracking performance which proves the feasibility and effectiveness of the proposed control scheme. Highlights: A hierarchical robust nonlinear controller is designed for an autonomous underwater vehicle (AUV). The controller is designed with the AUV subject to current disturbances, un-modeled dynamics, and parameter variations. The hierarchical controller uses a back-stepping controller in conjunction with a sliding-mode controller. The closed-loop stability of the proposed individual subsystems is guaranteed based on the Lyapunov stability criteria. The workability and robustness of the closed-loop system were validated using a 4 and 6-degree-of freedom models of the AUV.